2009
DOI: 10.4071/1551-4897-6.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Indium Transient Liquid Phase Sintering for High Temperature Die Attachment

Abstract: The demand for electronics capable of operating at temperatures above the traditional 125°C limit continues to increase. Devices based on wide band gap semiconductors have been demonstrated to operate at temperatures up to 500°C, but packaging remains a major hurdle to product development. Recent regulations, such as RoHS and WEEE, increase the complexity of the packaging task as they prohibit the use of certain materials in electronic products such as lead (Pb), which has traditionally been used in high tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The resulting IMCs melt at temperatures significantly higher than the operating temperatures seen in power modules. Because of this advantage, various TLP materials have been investigated for power module applications including nickeltin [20], gold-indium [23], silver-indium [24], silver-tin [25], and copper-tin [22]. However, double-sided TLP bonding has not yet been reported, especially for front-side bonding of power devices [11].…”
Section: Die-attachment Bonding Technologies For High Temperature Pow...mentioning
confidence: 99%
“…The resulting IMCs melt at temperatures significantly higher than the operating temperatures seen in power modules. Because of this advantage, various TLP materials have been investigated for power module applications including nickeltin [20], gold-indium [23], silver-indium [24], silver-tin [25], and copper-tin [22]. However, double-sided TLP bonding has not yet been reported, especially for front-side bonding of power devices [11].…”
Section: Die-attachment Bonding Technologies For High Temperature Pow...mentioning
confidence: 99%
“…It has been shown that solder pastes can be filled with Cu particles to achieve TLPS bonds [20]. AgIn pastes have also been used to form joints at low temperatures [21]. The joint strength at high temperatures has not yet been assessed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ag migration under bias at high temperature is also a reliability concern [9]. Transient liquid phase bonding (TLP) [10] has shown potential for die attach for temperatures up to 500°C [11], [12]. Many of the TLP systems are based on Au or Ag and are expensive and time consuming to process.…”
Section: Introductionmentioning
confidence: 99%